Public Health Interventions for Control of Malaria in the Population Living in the Terai Region of Nepal - Awasthi, Kiran Raj; Adefemi, Kazeem; Awasthi, Mamata Sherpa; Chalise, Binaya (Journal of Nepal Health Research Council, 2018)
Infectious diseases are a major problem for developing countries. Controlling and eradicating these diseases have remained a challenge because of the multitudes of social and environmental factors involved. However, a multi-sectoral and collective effort in dealing with these diseases has been shown to result in positive outcomes. This paper looks at the current situation of Malaria in Nepal and a population that is at high risk. It explains the impact that social and environmental determinants have on this target population. This review then critically examines the various possible public health interventions that could potentially help in the control of malaria in this high risk population, drawing from evidences and experiences reported from other countries with suggestions for adapting these interventions to the Nepali environment. Keywords: Indoor residual spray; long lasting Insecticide nets; malaria, mass media campaign; public health interventions; terai; Nepal.